Accelerating Urban Heating Under Land-Cover and Climate Change Scenarios in Indonesia: Application of the Universal Thermal Climate Index - Setiawati, Martiwi Diah; Jarzebski, Marcin Pawel; Gomez-Garcia, Martin; Fukushi, Kensuke (Frontiers in Built Environment, 2021)
Climate change and its effect on the frequency and magnitude of heat waves have huge impacts on urban population worldwide, including Indonesia where the population in urban areas is predicted to increase rapidly by 2050. Therefore, not only climate change mitigation measures are necessary but also adaptation solutions to more frequent extreme weather events such as these are essential at local levels. The projected increase of heat waves duration will increase health-related risk and it will drive growing energy demands particularly in urban areas. This is especially important due to a need for new solutions for growing urbanization that potentially increases urban heat island phenomenon. For this reason, analyzing the changing magnitude and spatial distribution of urban heat is essential for adequate adaptation planning. We projected the current and future spatial variability of heat stress index in three cities: Medan, Surabaya and Denpasar under climate change and land cover change scenarios and quantified it with Universal Thermal Climate Index (UTCI) for two periods, baseline (1981-2005) and future (2018 - 2042). Our results showed that currently the higher level of UTCI was identified in the urban centers of all three cities, indicating the contribution of urban heat island phenomenon to the higher UTCI. Under climate change scenario all three cities will experience increase of the heat, whereas applying the land cover scenario demonstrated that only Medan and Denpasar are likely to experience a higher increase of UTCI by 3.1 ºC, while in Surabaya the UTCI will decrease by 0.84 ºC in the period 2018 - 2042 due to urban greening. This study advanced the UTCI methodology demonstrating its applicability for urban heat warning systems and for monitoring of the urban greening cooling effect.